Cryopreservable, scalable and ready-to-use cell-laden patches for diabetic ulcer treatment - Bangrui Yu; Lanlan Peng; Wenjun Dang; Ying Fu; Zhijie Li; Jinteng Feng; Heng Zhao; Tian Wang; Feng Xu; Martin L. Yarmush; Haishui Huang (Bioactive Materials)
Stem cell-laden hydrogel patches are promising candidates to treat chronic ulcers due to cells’ long-lasting and dynamic responses to wound microenvironment. However, their clinical translations are prohibited by the cryopreservation difficulty due to their weak mechanical strength and slow biotransport capability, and by the morphological mismatch between clinical ulcers and pre-fabricated patches. Here we report a stem cell-laden alginate-dopamine hydrogel patch that can be readily cryopreserved, processed, and scaled toward clinical usages. This cell-hydrogel patch not only maintains cell viability and structure integrity during cryopreservation, but also can be directly utilized without centrifugation or incubation post cryopreservation. In addition, this tissue-adhesive hydrogel patch enables close wound contact and fast cellular response, and its scalable and flexible structure enables assembly for large or irregularly shaped ulcers. Therefore, it accelerates ulcer healing and reduces scar formation via continuous, versatile, self-adjusting paracrine of imbedded, cryopreserved stem cells. These findings highlight its potential for scalable clinical applications in chronic wound management and pave the way for broader adoption of ready-to-use regenerative therapies.